The heat of longevity: sex differences in lifespan and body temperature - Ruocco, Chiara; Ragni, Maurizio; Nisoli, Enzo (Frontiers in Pharmacology, 2024)
Dietary restriction (DR) has long been recognized as a powerful intervention for extending lifespan and improving metabolic health across species. In laboratory animals, DR-typically a 30-40% reduction in caloric intake-delays aging and enhances mitochondrial function, oxidative defense, and anti-inflammatory pathways. In humans, findings from the CALERIE™ trial confirm DR's potential benefits, with a 25% caloric reduction over two years resulting in reduced visceral fat, improved cardiometabolic health, and favorable gene expression changes linked to proteostasis, DNA repair, and inflammation. However, recent research in genetically diverse mouse populations reveals that the impact of DR on lifespan is substantially modulated by genetic background, underscoring the importance of individual variability. Additionally, emerging evidence challenges previous assumptions that lower body temperature universally benefits lifespan extension, with data indicating complex relationships between thermoregulation, sex, and longevity. These findings underscore the need for nuanced approaches to DR in both research and potential therapeutic applications, with considerations for genetic and sex-specific factors to maximize healthspan and lifespan outcomes.